Water-based polyacrylic resin for color stone metal tile as well as preparation method and application of water-based polyacrylic resin

By designing a water-based polyacrylic resin containing functional sticky carboxyl groups, hydroxyl groups and wet adhesion phosphoric acid functional groups, and optimizing the polymerization process and components, we solved the problems of weak adhesion of colored stone metal tiles and easy falling off of colored sand. , significantly improving its water resistance, bending resistance and UV resistance.

CN119350554APending Publication Date: 2025-01-24SHANDONG BAISHENG METAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411626525.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing colored stone metal tiles have weak bonding power, easy colored sand to fall off, poor water resistance, poor bending resistance, easy yellowing and changing when exposed to ultraviolet rays, and obvious hot stickiness, cold and brittleness, which limits its widespread application.

Method used

By designing the combination of butyl methacrylate and isooctyl acrylate, a comb-type water-based polyacrylic resin skeleton is obtained, and itaconic acid, hydroxypropyl methacrylate and acrylic phosphate monomers are introduced to synergistically introduce functional sticky carboxyl groups, Hydroxyl and wet adhesion phosphate functional groups improve bonding properties. In the polymerization process, the polymerization process is first nucleated, and then the zinc methacrylate cross-linking component is optimized and controlled to enhance the bonding performance with the galvanized steel plate, and the calcium fluoride component is introduced to improve the bottom gripping and bonding properties.

Benefits of technology

Significantly improves the bonding performance of colored stone metal tiles, solves the problem of easy shedding of colored sand, enhances water resistance and bending resistance, improves tolerance to ultraviolet rays, reduces hot sticking and cold brittleness, and improves The overall performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350554A_ABST
    Figure CN119350554A_ABST
Patent Text Reader

Abstract

The invention discloses water-based polyacrylic resin for color stone metal tiles and a preparation method and application thereof, and belongs to the field of novel functional water-based paint coatings for building materials, the water-based polyacrylic resin for color stone metal tiles is prepared from the following raw materials in parts by mass: 30.0-55.0 parts of acrylate monomer, 1.0-10.0 parts of acrylic acid (ester) functional monomer, 1.0-10.0 parts of acrylic acid (ester) functional monomer, 1.0-10.0 parts of acrylic acid (ester) functional monomer, 1.0-10.0 parts of acrylic acid (ester) functional monomer, 1.0-10.0 parts of acrylic acid (ester) functional monomer, 1.0-10.0 parts of acrylic acid 1.0 to 10.0 parts of a special functional monomer, 1.0 to 4.0 parts of a reactive emulsifier, 0.1 to 1.0 part of an initiator and 40.0 to 60.0 parts of water; the special functional monomer comprises an acrylic phosphate monomer and zinc methacrylate. Through the structural design of key water-based polyacrylic resin for a water-based coating for a color stone metal tile, the water-based polyacrylic resin which has excellent bottom grasping property and strong binding force on an aluminum-zinc plated steel plate for a color stone metal tile base material is obtained, and then the water-based polyacrylic resin is prepared by regulating and controlling auxiliary components such as the filler, the dispersing agent and the thickening agent. The water-based coating for the high-performance color stone metal tile is obtained, the result shows that the core problems that the color stone metal tile is weak in binding power and color sand is prone to falling off are effectively solved, and therefore the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional water-based paint coatings for new building materials, and particularly relates to a water-based polyacrylic acid resin for colored stone metal tiles and a preparation method and application thereof. Background Art

[0002] Traditional clay tiles are made of clay and other synthetic materials into wet embryos, which are then dried and fired at high temperatures. They are widely used in my country's construction industry because they are easy to obtain from local materials and have simple production processes. However, in recent years, traditional clay tiles have been restricted and gradually banned by the state due to their high energy consumption and pollution in the preparation process, as well as their own shortcomings such as being heavy, easy to fall off, damaged and polluted. Colored stone metal tiles are a new type of green roofing material that has developed rapidly in recent years to replace traditional clay tiles. They have become the mainstream product of international roofing materials. Colored stone metal tiles are a new generation of metal roofing materials made of highly corrosion-resistant aluminum-zinc-coated steel plates as the base material, high-quality water-based acrylic resins as adhesives, highly weather-resistant natural colored stone particles (basalt particles) or natural gravel dyed with inorganic pigments as the surface layer. They are processed by special processes and are suitable for slope roof projects of various styles and structures (wooden structures, steel structures and concrete structures), as well as for projects such as flat-to-slope conversion of existing buildings, renovation of old roofs and partial decoration of buildings.

[0003] With the increasing application and promotion of colored stone metal tiles, a large number of long-term engineering practices have shown that colored stone metal tiles as roof decoration materials will face complex weather conditions such as high temperature, humidity, rain and snow, so there are more or less certain defects and deficiencies, mainly manifested in weak bonding, easy falling off of colored sand, poor water resistance, poor bending resistance, easy yellowing under ultraviolet radiation, hot stickiness and cold brittleness, etc. These defects greatly limit the wide application of colored stone metal tiles. The reason is that the performance of colored stone metal tiles mainly depends on the performance of the water-based acrylic resin adhesive used. In the prior art, polyacrylic acid emulsion is mainly used as the adhesive of colored stone metal tiles. Although polyacrylic acid emulsion has obvious cost advantages, its bonding force to the metal substrate is poor, which causes the colored stone to fall off easily; at the same time, the water absorption rate of polyacrylic acid emulsion after drying and film formation is high, which makes the colored stone metal tiles very easy to debond and expose the bottom under external force after soaking in water. Serious quality accidents, especially unsuitable for use in areas with heavy rain and humid climate.

[0004] Therefore, the performance of polyacrylic acid emulsion as the bonding base resin of colored stone metal tiles directly determines the comprehensive performance of colored stone metal tiles. At present, the bonding base resins for colored stone metal tiles on the market are mainly divided into styrene acrylic, pure acrylic and acetate acrylic emulsions. Due to the large differences in synthesis process, molecular weight distribution and particle size of different types of emulsions, the performance of different emulsion systems is also significantly different. Summary of the invention

[0005] The purpose of the present invention is to provide a water-based polyacrylic resin for colored stone metal tiles and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art. The present invention firstly obtains a comb-shaped water-based polyacrylic resin skeleton by designing the combination of butyl methacrylate and isooctyl acrylate, and then introduces functional sticky carboxyl, hydroxyl and wet adhesion phosphoric acid functional groups through itaconic acid, hydroxypropyl methacrylate and phosphate acrylate monomers, thereby significantly improving its bonding performance to the aluminum-zinc-coated steel plate substrate; secondly, in the polymerization process, butyl methacrylate, isooctyl acrylate, itaconic acid, hydroxypropyl methacrylate and phosphate acrylate monomers are first polymerized into nuclei, and then the zinc methacrylate cross-linking component is optimized and regulated, which not only effectively realizes the stability of the water-based polyacrylic resin, but also further enhances the homogeneous and efficient complex bonding with the aluminum-zinc-coated steel plate for the colored stone metal tile by zinc ion complexation; finally, the introduction of the calcium fluoride component effectively increases the surface penetration of the aluminum-zinc-coated steel plate, and further improves the bottom grip and bonding performance of the water-based coating for the colored stone metal tile; the high-performance water-based coating for the colored stone metal tile obtained by the present invention effectively solves the core problem of easy shedding of colored sand and poor bonding performance, and thus has broad application prospects.

[0006] One of the technical solutions provided by the present invention:

[0007] A water-based polyacrylic resin for colored stone metal tiles comprises the following raw materials, measured by weight: 30.0 to 55.0 parts of acrylate monomers, 1.0 to 10.0 parts of acrylic (ester) functional monomers, 1.0 to 10.0 parts of special functional monomers, 1.0 to 4.0 parts of reactive emulsifiers, 0.1 to 1.0 parts of initiators and 40.0 to 60.0 parts of water; the special functional monomers comprise acrylic acid phosphate monomers and zinc methacrylate.

[0008] Furthermore, the water-based polyacrylic resin used for the colored stone metal tiles includes the following raw materials, calculated by mass: 35.0 to 40.0 parts of acrylate monomers, 3.0 to 8.0 parts of acrylic (ester) functional monomers, 2.0 to 6.0 parts of special functional monomers, 1.5 to 3.0 parts of reactive emulsifiers, 0.2 to 0.5 parts of initiators and 45.0 to 55.0 parts of deionized water.

[0009] Furthermore, the acrylic acid ester monomer comprises 20.0 to 30.0 parts of butyl methacrylate and 10.0 to 15.0 parts of isooctyl acrylate, calculated by weight.

[0010] Furthermore, the acrylic acid (ester) functional monomer includes 1.0 to 3.0 parts of conic acid and 2.0 to 5.0 parts of hydroxypropyl methacrylate;

[0011] Furthermore, the special functional monomer includes 1.0 to 3.0 parts of acrylic acid phosphate monomer and 1.0 to 3.0 parts of zinc methacrylate;

[0012] The present invention optimizes and modifies the traditional water-based polyacrylic resin based on the design of polymer molecular structure, innovatively screens and designs the use of butyl methacrylate and isooctyl acrylate to obtain a comb-shaped water-based polyacrylic resin skeleton, and at the same time, functional sticky carboxyl, hydroxyl and wet adhesion phosphoric acid functional groups are synergistically introduced through itaconic acid, hydroxypropyl methacrylate and acrylic acid phosphate monomers, thereby significantly improving the bonding performance of the water-based polyacrylic resin to the aluminum-zinc-plated steel plate substrate.

[0013] Furthermore, the initiator is ammonium persulfate, potassium persulfate or sodium persulfate, preferably potassium persulfate.

[0014] Furthermore, the reactive emulsifier is one of Aidico SR-10, Solvay's COPS-1, Double Bond Chemical's DNS-86, Solvay AES100, sodium vinyl sulfonate (SVS), and sodium styrene sulfonate. It should also be noted that anionic emulsifiers cannot be used in this reaction system; preferably, the reactive emulsifier is a combination of Aidico SR-10 and sodium styrene sulfonate, and the amount of SR-10 is 0.5 to 1.0 parts, and the amount of sodium styrene sulfonate is 1.0 to 2.0 parts.

[0015] The second technical solution provided by the present invention is:

[0016] A preparation method of the above-mentioned water-based polyacrylic resin for colored stone metal tiles, the preparation method is a pre-emulsification polymerization process, comprising the following steps: weighing raw materials according to mass parts, mixing a reactive emulsifier, a part of deionized water and an initiator, stirring evenly, adding acrylate monomers, acrylic acid (ester) functional monomers and acrylic acid phosphate monomers, emulsifying to obtain a pre-emulsion; heating the remaining deionized water, starting to drip the pre-emulsion, controlling the dripping time, continuing to heat after the dripping is completed, adding zinc methacrylate after the insulation reaction, continuing the reaction, and ending the reaction. After cooling, remove the residual monomers, adjust the pH value and filter to remove impurities to prepare the water-based polyacrylic resin for colored stone metal tiles.

[0017] The polymerization process of the water-based polyacrylic resin used for the colored stone metal tile of the present invention is also different from the traditional polymerization process. The prominent performance is that butyl methacrylate, isooctyl acrylate, itaconic acid, hydroxypropyl methacrylate and acrylic acid phosphate monomers are first polymerized into a nucleus, and then the cross-linking component zinc methacrylate is added later by optimizing and regulating. Not only the stability of the water-based polyacrylic resin is effectively achieved, but also the effective introduction of complex zinc ions further achieves homogeneous and efficient complex bonding with the aluminum-zinc-coated steel plate used for the colored stone metal tile.

[0018] Further, the heating is heating to 81°C, the continued heating is heating to 86°C, and the cooling is cooling to 60°C;

[0019] Furthermore, the emulsification time is 0.5h;

[0020] Furthermore, the dropping time is 2.5h;

[0021] Furthermore, the heat preservation reaction time is 1h;

[0022] Furthermore, the continued reaction is 1h;

[0023] Furthermore, the pH value is 7-8.

[0024] The third technical solution provided by the present invention is:

[0025] A use of the aqueous polyacrylic resin for colored stone metal tiles in preparing aqueous coatings for colored stone metal tiles.

[0026] The fourth technical solution provided by the present invention is:

[0027] A water-based coating for colored stone metal tiles comprises, by weight, 20.0 to 50.0 parts of the water-based polyacrylic resin for the colored stone metal tiles, 10.0 to 40.0 parts of fillers, 1.0 to 5.0 parts of dispersants, 0.2 to 1.5 parts of defoamers, 1.0 to 5.0 parts of thickeners, 0.1 to 1.5 parts of color pastes and 10.0 to 30.0 parts of deionized water.

[0028] Furthermore, the aqueous coating for the colored stone metal tiles includes, by mass, 30.0 to 45.0 parts of the aqueous polyacrylic resin for the colored stone metal tiles, 20.0 to 35.0 parts of fillers, 1.5 to 3.0 parts of dispersants, 0.3 to 1.0 parts of defoaming agents, 1.5 to 3.0 parts of thickeners, 0.3 to 1.0 parts of color pastes and 15.0 to 25.0 parts of deionized water.

[0029] Aiming at the core problem that the colored stone metal tile has weak bonding force and the colored sand is easy to fall off, the invention uses the prepared aqueous polyacrylic acid resin for the colored stone metal tile as a raw material to prepare the aqueous coating for the colored stone metal tile.

[0030] The present invention starts with the design and preparation of polymer molecular structure, uses acrylate monomers, acrylic acid (ester) functional monomers and special functional monomers to prepare water-based polyacrylic resin through emulsion polymerization process, and then prepares water-based coating for colored stone metal tiles with the aid of inorganic components and auxiliary components (dispersant, defoamer, bactericidal and mildewproof agent, thickener and color paste, etc.).

[0031] The present invention also optimizes the filler component of the water-based coating for colored stone metal tiles, innovatively introduces a calcium fluoride component, and the effective introduction of fluoride ions increases the surface penetration effect of the coating on the galvanized steel plate, further improving the bottom gripping efficiency and bonding performance of the water-based coating for colored stone metal tiles.

[0032] Furthermore, the filler is formed by mixing heavy calcium carbonate, calcined kaolin and calcium fluoride in a mass ratio of 3.0:6.0:1.0; preferably, the heavy calcium carbonate, calcined kaolin and calcium fluoride are all 800 mesh.

[0033] Furthermore, the dispersant is a melamine water reducer;

[0034] Further, the defoamer is a silicone type defoamer;

[0035] Furthermore, the thickener is an alkali swelling thickener or a polyurethane thickener;

[0036] Furthermore, the color paste is phthalocyanine blue, iron red, chrome yellow or carbon black.

[0037] The fifth technical solution provided by the present invention is:

[0038] A method for preparing the above-mentioned water-based coating for colored stone metal tiles comprises the following steps: weighing raw materials according to mass parts, adding water-based polyacrylic resin for colored stone metal tiles into deionized water, stirring, adding defoaming agent and dispersant, continuing stirring, and slowly adding filler, stirring sufficiently, dripping thickener diluted with deionized water, adding color paste until the viscosity reaches 100±10ku, and finally stirring to obtain the water-based coating for colored stone metal tiles.

[0039] Furthermore, the stirring and continued stirring times are both 10 minutes, and the sufficient stirring and final stirring times are both 30 minutes.

[0040] The sixth technical solution provided by the present invention is:

[0041] An application of the water-based coating of the colored stone metal tile in the field of roof decoration of new building materials.

[0042] Compared with the prior art, the present invention has the following advantages and technical effects:

[0043] The present invention obtains an aqueous polyacrylic resin with excellent bottom grip and strong adhesion to the aluminum-zinc-coated steel plate used as the substrate of the colored stone metal tile through the structural design of the key aqueous polyacrylic resin for the aqueous coating of the colored stone metal tile, and then obtains a high-performance aqueous coating for the colored stone metal tile by adjusting the auxiliary components such as fillers, dispersants and thickeners. The results show that the present invention effectively solves the core problem of weak adhesion of the colored stone metal tile and easy shedding of the colored sand. In addition, the present invention eliminates vinyl monomers containing benzene rings such as styrene in conventional coatings and selects aqueous polyacrylate resins prepared by acrylate, acrylic acid (ester) functional monomers and special functional monomers, so that the prepared aqueous coating for the colored stone metal tile has anti-ultraviolet performance and is more suitable for outdoor applications, and thus has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0045] Figure 1 This is a sand shoveling test image of the colored stone metal tile prepared in Example 11 before any treatment;

[0046] Figure 2 This is a test picture of the colored stone metal tile prepared in Example 11 after being soaked in water and dried;

[0047] Figure 3 This is a test diagram of the colored stone metal tile prepared in Example 11 after being boiled and cooled and then shoveled;

[0048] Figure 4 This is a 180° bending test diagram of the colored stone metal tile prepared in Example 11;

[0049] Figure 5 This is a sand shoveling test image of the colored stone metal tile prepared in Example 13 before any treatment;

[0050] Figure 6 This is a sand shoveling test image of the colored stone metal tile prepared in Example 13 after being soaked in water and dried;

[0051] Figure 7 This is a test diagram of the colored stone metal tile prepared in Example 13 after being boiled and cooled and then shoveled;

[0052] Figure 8 This is a 180° bending test diagram of the colored stone metal tile prepared in Example 13;

[0053] Fig. 9 This is a 180° bending test diagram of the colored stone metal tile prepared in Example 17;

[0054] Fig.10 This is a test image of the colored stone metal tile shoveling sand prepared in Example 17. DETAILED DESCRIPTION

[0055] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0056] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0057] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0058] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0059] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0060] In the embodiments of the present invention, “parts” refer to “parts by mass” unless otherwise specified.

[0061] All raw materials in the embodiments of the present invention were purchased, wherein the dispersant was a melamine water reducer (F10, BASF); the defoamer was a silicone defoamer (BYK-028, BYK); and the thickener was an alkali swelling thickener (L344, Akzo Nobel) or a polyurethane thickener (ViscoPlus, Digo).

[0062] Example 1

[0063] Add 0.5kg SR-10 reactive emulsifier, 17.0kg deionized water, 2.0kg sodium styrene sulfonate into the pre-emulsification kettle, stir until completely dissolved, then add 0.25kg potassium persulfate initiator, stir and mix, then add 23.0kg butyl methacrylate, 15.0kg isooctyl acrylate, 1.5kg itaconic acid, 2.0kg hydroxypropyl methacrylate and 1.0kg PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, emulsify for 0.5h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, and after the dripping is completed, heat to 86°C, keep warm for 1h, add 2.0kg of zinc methacrylate, continue to react for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%, the same below), filter and remove impurities with an 80-mesh filter to obtain a water-based polyacrylic resin for colored stone metal tiles.

[0064] Example 2

[0065] In the pre-emulsification kettle, 0.8 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water were added, and 2.0 kg of sodium styrene sulfonate was added, and stirred to dissolve completely. Then, 0.25 kg of potassium persulfate initiator was added, and stirred to mix well. Then, 23.0 kg of butyl methacrylate, 15.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.0 kg of PAM-100 acrylic acid phosphate monomer were added to the pre-emulsification kettle in sequence, and emulsified for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drop the pre-emulsion, control the dropping time to 2.5h, raise the temperature to 86°C after the dropping is completed, keep warm for 1h, add 2.0kg of zinc methacrylate, continue the reaction for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water, filter through an 80-mesh filter to remove impurities, and obtain a water-based polyacrylic resin for colored stone metal tiles.

[0066] Example 3

[0067] Add 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water into the pre-emulsification kettle, add 2.0 kg of sodium styrene sulfonate, stir to dissolve it completely, then add 0.25 kg of potassium persulfate initiator, stir to mix, then add 23.0 kg of butyl methacrylate, 15.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.0 kg of PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, and emulsify for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drop the pre-emulsion, control the dropping time to 2.5h, raise the temperature to 86°C after the dropping is completed, keep warm for 1h, add 2.0kg of zinc methacrylate, continue the reaction for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water, filter through an 80-mesh filter to remove impurities, and obtain a water-based polyacrylic resin for colored stone metal tiles.

[0068] Example 4

[0069] Add 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water into the pre-emulsification kettle, add 2.0 kg of sodium styrene sulfonate, stir to dissolve it completely, then add 0.25 kg of potassium persulfate initiator, stir to mix, then add 23.0 kg of butyl methacrylate, 15.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.5 kg of PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, and emulsify for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, and after the dripping is completed, heat to 86°C, keep warm for 1h, add 2.3kg of zinc methacrylate, continue to react for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter with 80-mesh filter to remove impurities, and obtain water-based polyacrylic resin for colored stone metal tiles.

[0070] Example 5

[0071] Add 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water into the pre-emulsification kettle, add 2.0 kg of sodium styrene sulfonate, stir to dissolve it completely, then add 0.25 kg of potassium persulfate initiator, stir to mix, then add 25.0 kg of butyl methacrylate, 13.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.5 kg of PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, and emulsify for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, and after the dripping is completed, heat to 86°C, keep warm for 1h, add 2.3kg of zinc methacrylate, continue to react for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter with 80-mesh filter to remove impurities, and obtain water-based polyacrylic resin for colored stone metal tiles.

[0072] Example 6

[0073] Add 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water into the pre-emulsification kettle, add 2.0 kg of sodium styrene sulfonate, stir to dissolve it completely, then add 0.25 kg of potassium persulfate initiator, stir to mix, then add 25.0 kg of butyl methacrylate, 13.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.5 kg of hydroxypropyl methacrylate, and 1.5 kg of PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, and emulsify for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, and after the dripping is completed, heat to 86°C, keep warm for 1h, add 2.3kg of zinc methacrylate, continue to react for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter with 80-mesh filter to remove impurities, and obtain water-based polyacrylic resin for colored stone metal tiles.

[0074] Comparative Example 1

[0075] Add 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water into the pre-emulsification kettle, add 2.0 kg of sodium styrene sulfonate, stir to dissolve it completely, then add 0.25 kg of potassium persulfate initiator, stir to mix, then add 38.0 kg of butyl methacrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.5 kg of PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, and emulsify for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, and after the dripping is completed, heat to 86°C, keep warm for 1h, add 2.3kg of zinc methacrylate, continue to react for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter with 80-mesh filter to remove impurities, and obtain water-based polyacrylic resin for colored stone metal tiles.

[0076] Comparative Example 2

[0077] Add 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water into the pre-emulsification kettle, add 2.0 kg of sodium styrene sulfonate, stir to dissolve it completely, then add 0.25 kg of potassium persulfate initiator, stir to mix, then add 25.0 kg of butyl methacrylate, 13.0 kg of butyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.5 kg of PAM-100 acrylic acid phosphate monomer into the pre-emulsification kettle in turn, and emulsify for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, and after the dripping is completed, heat to 86°C, keep warm for 1h, add 2.3kg of zinc methacrylate, continue to react for 1h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter with 80-mesh filter to remove impurities, and obtain water-based polyacrylic resin for colored stone metal tiles.

[0078] Comparative Example 3

[0079] In the pre-emulsification kettle, 1.0 kg of SR-10 reactive emulsifier and 17.0 kg of deionized water were added, and 2.0 kg of sodium styrene sulfonate was added, and stirred to dissolve completely. Then, 0.25 kg of potassium persulfate initiator was added, and stirred to mix well. Then, 25.0 kg of butyl methacrylate, 13.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, 1.5 kg of PAM-100 acrylic acid phosphate monomer, and 2.3 kg of zinc methacrylate were added to the pre-emulsification kettle in sequence, and emulsified for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drip the pre-emulsion, control the dripping time to 2.5h, heat to 86°C after the dripping is completed, continue to keep warm for 2h, then end the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in turn to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter with 80-mesh filter to remove impurities, and obtain water-based polyacrylic resin for colored stone metal tiles.

[0080] Comparative Example 4

[0081] In the pre-emulsification kettle, 1.0 kg of SR-10 reactive emulsifier, 1.0 kg of CO436 anionic emulsifier, and 17.0 kg of deionized water were added, and 1.0 kg of sodium styrene sulfonate was added, and stirred to dissolve it completely. Then, 0.25 kg of potassium persulfate initiator was added, and stirred to mix well. Then, 25.0 kg of butyl methacrylate, 13.0 kg of isooctyl acrylate, 1.5 kg of itaconic acid, 2.0 kg of hydroxypropyl methacrylate, and 1.5 kg of PAM-100 acrylic acid phosphate monomer were added to the pre-emulsification kettle in turn, and emulsified for 0.5 h to obtain a pre-emulsion. Then add 35.0kg of deionized water into the polymerization reactor, stir and heat to 81°C, start to drop the pre-emulsion, control the dropping time to 2.5h, raise the temperature to 86°C after the dropping is completed, keep warm for reaction for 1h, add 2.3kg of zinc methacrylate, continue the reaction for 1h, then terminate the reaction, cool to 60°C, then add 0.15kg of tert-butyl hydroperoxide and 0.5kg of Rongalite aqueous solution (10wt.%) in sequence to remove residual monomers in the system, adjust the pH to 7.5 with ammonia water (concentration of 20wt.%), filter through an 80-mesh filter to remove impurities, and obtain the water-based polyacrylic resin for colored stone metal tiles.

[0082] Example 7

[0083] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 1, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0084] Example 8

[0085] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 2, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0086] Example 9

[0087] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 3, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0088] Example 10

[0089] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 4, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0090] Embodiment 11

[0091] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 5, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0092] Example 12

[0093] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 6, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0094] Example 13

[0095] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Comparative Example 1, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener dropwise into the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0096] Embodiment 14

[0097] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Comparative Example 2, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in turn, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in turn, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener dropwise into the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0098] Embodiment 15

[0099] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Comparative Example 3, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in turn, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 2.9 kg of calcium fluoride in turn, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener dropwise into the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0100] Example 16

[0101] Add 24.0kg of deionized water to the stirring kettle, then add 43.0kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Comparative Example 4, stir for 10 minutes, then add 0.7kg BYK-028 defoamer and 2.0kg F10 dispersant in turn, stir for 10 minutes, continue to slowly add 8.7kg of heavy calcium, 17.4kg of calcined kaolin, and 2.9kg of calcium fluoride in turn, stir well for 30 minutes, and then slowly add 1.5kg of PUR-50 thickener dropwise into the stirring kettle until the viscosity reaches 100±10ku, then add 0.5kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0102] Embodiment 17

[0103] Add 24.0 kg of deionized water to the stirring kettle, then add 43.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 5, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 3.0 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener dropwise into the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0104] Embodiment 18

[0105] Add 24.0 kg of deionized water to the stirring kettle, then add 44.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 5, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 8.7 kg of heavy calcium, 17.4 kg of calcined kaolin, and 3.0 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0106] Embodiment 19

[0107] Add 25.0 kg of deionized water to the stirring kettle, then add 44.0 kg of the aqueous polyacrylic resin for colored stone metal tiles prepared in Example 5, stir for 10 minutes, then add 0.7 kg of BYK-028 defoamer and 2.0 kg of F10 dispersant in sequence, stir for 10 minutes, continue to slowly add 12 kg of heavy calcium, 18.0 kg of calcined kaolin, and 3.0 kg of calcium fluoride in sequence, stir well for 30 minutes, and then slowly add 1.5 kg of PUR-50 thickener to the stirring kettle until the viscosity reaches 100 ± 10 ku, then add 0.5 kg of carbon black slurry, and continue stirring for 30 minutes to obtain a high-performance aqueous coating for colored stone metal tiles.

[0108] Performance test

[0109] In view of the fact that there is no national standard in the colored stone metal tile industry, the present invention refers to the industry standard JCT2470-2018 colored stone metal tiles and relevant national standards (GBT20623-2006 emulsion for building coatings, GBT16777-2008 test method for building waterproof coatings, GBT23445-2009 polymer cement waterproof coatings), and is appropriately revised and improved in combination with actual market needs. The prepared water-based polyacrylic resin and high-performance colored stone metal tile water-based coating are subjected to performance tests. At the same time, the particle size and distribution of the high-performance colored stone metal tiles and their water-based polyacrylic resins are tested using a dynamic light scattering instrument (DLS).

[0110] Table 1 shows the appearance, stability, particle size and distribution of the aqueous polyacrylic resin used in the colored stone metal tiles prepared in Examples 1-6 and Comparative Examples 1-4 of the present invention.

[0111] Table 1

[0112]

[0113]

[0114] As shown in Table 1, the aqueous polyacrylic resin emulsions of the colored stone metal tiles prepared in Examples 1-6 and Comparative Examples 1-3 of the present invention meet the requirements in terms of appearance, stability and emulsion particle size. Comparative Example 4 has a higher gel content and a larger particle size.

[0115] In order to evaluate the water resistance of the water-based polyacrylic resin for colored stone metal tiles, the present invention refers to the industry standard JC / T1017-2006 "Polymer Emulsion for Building Waterproof Coatings" to measure the water absorption of the water-based polyacrylic resin for the colored stone metal tiles prepared in Examples 1-6 and Comparative Examples 1-4. Table 2 shows the water resistance measurement results of the water-based polyacrylic resin for the above-mentioned high-performance colored stone metal tiles.

[0116] Table 2

[0117]

[0118] It can be seen from Table 2 that the water-based polyacrylic resin used in the colored stone metal tiles prepared in Examples 1-6 of the present invention has excellent water resistance, low water absorption of the coating film, and the water absorption of the coating film after 72 hours is less than 15%. At the same time, the present invention also provides a series of comparative examples, among which, comparative example 1 only changes the type of acrylate monomer and uses butyl methacrylate for all of them, comparative example 2 maintains the acrylate monomer ratio and replaces propylene isooctyl ester with butyl acrylate, comparative example 3 emulsifies and adds acrylate monomer, acrylic acid (ester) functional monomer and special functional monomer together, and comparative example 4 changes the emulsifier system. The water absorption results show that the water absorption of comparative examples 1, 2, 3, and 4 is significantly higher than that of preferred embodiments 1-6 of the present invention, which further illustrates that the present invention optimizes and regulates the types and ratios of acrylate monomers, acrylic acid (ester) functional monomers, and special functional monomers, polymerization processes, and the types and ratios of emulsifier systems, and synergistically introduces functional sticky carboxyl groups, hydroxyl groups, and wet adhesion phosphoric acid functional groups, while improving the bonding performance of the water-based polyacrylic resin to the aluminum-zinc-plated steel plate substrate. The effective cross-linking and bonding of special functional monomers improves the polymer cross-linking network of the water-based acrylic resin and improves its water resistance. Therefore, this provides a solid foundation for the excellent water resistance of the subsequent colored stone metal tiles based on the water-based polyacrylic resin.

[0119] A large number of practices have shown that colored stone metal tiles have weak bonding strength, easy detachment of colored sand, poor water resistance and poor bending resistance due to the influence of complex weather conditions such as high temperature, humidity, rain and snow. Therefore, the present invention uses the aqueous coating prepared in Examples 7-19 to coat the colored stone metal tiles respectively, and further characterizes and evaluates the mechanical properties of the colored stone metal tiles prepared based on the aqueous polyacrylic resin, such as 180° bending and water resistance, such as boiling (100°C, 2h) and blister (24°C, 24h). Table 3 shows the mechanical and water resistance test results of the high-performance colored stone metal tiles prepared in Examples 7-19 of the present invention.

[0120] Table 3

[0121]

[0122]

[0123] It can be seen from Table 3 that the colored stone metal tiles based on the water-based polyacrylic resin prepared in Examples 7-12 and 17-19 of the present invention do not lose sand or expose the bottom when bent 180°, and have excellent bonding properties after boiling in water (100°C, 2h) and soaking in water (24°C, 24h), without any phenomenon such as losing sand, exposing the bottom or falling off.

[0124] As shown in Table 3, the water-based coatings for colored stone metal tiles prepared from the water-based polyacrylic resins prepared from Comparative Examples 1-4 respectively have very poor 180° bending performance, sand-adhesive performance after boiling (100°C, 2h) and cooling after soaking (24°C, 24h), and are generally prone to sand shedding, bottom exposure, and whitening. Combined with the water absorption test results of the aforementioned water-based polyacrylates, it is shown that the present invention optimizes and controls the types and ratios of acrylate monomers, acrylic acid (ester) functional monomers, and special functional monomers, polymerization processes, and the types and ratios of emulsifier systems to obtain a series of water-based polyacrylic resins that are different from traditional water-based polyacrylic resins and have excellent bottom grip and strong adhesion to aluminum-zinc steel plates used as colored stone metal tile substrates, and then controls components such as fillers and thickeners to obtain a high-performance water-based coating for colored stone metal tiles.

[0125] Figure 1 This is a sand shoveling test diagram of the colored stone metal tile prepared in Example 11 before any treatment; it can be seen from the figure that the water-based polyacrylic resin coating has high strength and toughness, strong adhesion to the substrate aluminum-zinc-coated steel plate, and no bottom is exposed in the sand shoveling destruction test, so it has excellent performance.

[0126] Figure 2 This is a sand shoveling test diagram of the colored stone metal tile prepared in Example 11 after being soaked in water and dried; it can be seen from the figure that although the adhesion between the water-based polyacrylic resin coating and the substrate aluminum-zinc-coated steel plate is reduced after soaking in water, the sand shoveling damage test only slightly exposes the bottom, and at the same time, the strength and toughness of the water-based polyacrylic resin coating are still very excellent, so the performance is excellent.

[0127] Figure 3 This is a sand shoveling test diagram of the colored stone metal tile prepared by Example 11 after being boiled in water and cooled; it can be seen from the figure that the bottom adhesion, strength and toughness of the water-based polyacrylic resin coating after boiling in water do not decrease significantly, which is similar to the result of blisters, so the water-based polyacrylic resin coating has excellent water boiling resistance.

[0128] Figure 4This is a 180° bending test diagram of the colored stone metal tile prepared by Example 11; it can be seen from the figure that the water-based polyacrylic resin coating has excellent bending resistance, that is, no cracking and no sand falling. This is because the present invention obtains a comb-shaped water-based polyacrylic resin skeleton by optimizing the ratio of butyl methacrylate and isooctyl acrylate, and at the same time, in the polymerization process, butyl methacrylate, isooctyl acrylate, itaconic acid, hydroxypropyl methacrylate and acrylic acid phosphate monomers are first polymerized into nuclei, and then the zinc methacrylate cross-linking component is optimized and regulated, which not only effectively realizes the formation of soft, hard and cross-linked polymer networks of water-based polyacrylic resin, but also exhibits excellent strength and toughness.

[0129] Figure 5 This is a sand shoveling test diagram of the colored stone metal tile prepared by Example 13 before any treatment; it can be seen from the figure that the water-based polyacrylic resin coating has good strength and toughness, and the bottom is not exposed in the sand shoveling damage test, so the performance is excellent.

[0130] Figure 6 This is a sand shoveling test diagram of the colored stone metal tile prepared by Example 13 after being soaked in water and dried; it can be seen from the figure that after soaking in water, the adhesion between the water-based polyacrylic resin coating and the substrate aluminum-zinc-coated steel plate is poor, and the bottom is obviously exposed in the sand shoveling destruction test, so the performance is poor.

[0131] Figure 7 This is a sand shoveling test diagram of the colored stone metal tile prepared in Example 13 after being boiled in water and cooled; it can be seen from the figure that the result is similar to the water bubble result, so the water-based polyacrylic resin coating has poor water boiling resistance.

[0132] Figure 8 This is a 180° bending test diagram of the colored stone metal tile prepared in Example 13; it can be seen from the figure that the bending resistance of the water-based polyacrylic resin coating is poor, and cracking and sand loss are obvious.

[0133] Fig. 9 This is a 180° bending test diagram of the colored stone metal tile prepared in Example 17; it can be seen from the figure that the water-based polyacrylic resin coating has excellent bending resistance, that is, it does not crack or fall off.

[0134] Fig.10 This is a sand shoveling test diagram of the colored stone metal tile prepared in Example 17. It can be seen from the figure that the water-based polyacrylic resin coating has high strength and toughness, and has strong adhesion to the substrate aluminum-zinc-coated steel plate. The bottom is not exposed in the sand shoveling destruction test, so the performance is excellent.

[0135] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A water-based polyacrylic resin for colored stone metal tiles, characterized in that: The raw materials include, by weight: 30.0 to 55.0 parts of acrylate monomer, 1.0 to 10.0 parts of acrylic acid (ester) functional monomer, 1.0 to 10.0 parts of special functional monomer, 1.0 to 4.0 parts of reactive emulsifier, 0.1 to 1.0 parts of initiator and 40.0 to 60.0 parts of water; The special functional monomers include acrylic acid phosphate monomers and zinc methacrylate.

2. The water-based polyacrylic resin for colored stone metal tiles according to claim 1, characterized in that: According to the weight percentage, it includes the following raw materials: 35.0-40.0 parts of acrylate monomer, 3.0-8.0 parts of acrylic acid (ester) functional monomer, 2.0-6.0 parts of special functional monomer, 1.5-3.0 parts of reactive emulsifier, 0.2-0.5 parts of initiator and 45.0-55.0 parts of deionized water.

3. The aqueous polyacrylic resin for colored stone metal tiles according to claim 2, characterized in that: The acrylate monomer comprises 20.0 to 30.0 parts by weight of butyl methacrylate and 10.0 to 15.0 parts by weight of isooctyl acrylate; and / or The acrylic acid (ester) functional monomer comprises 1.0 to 3.0 parts of itaconic acid and 2.0 to 5.0 parts of hydroxypropyl methacrylate; and / or The special functional monomers include 1.0 to 3.0 parts of acrylic acid phosphate monomers and 1.0 to 3.0 parts of zinc methacrylate.

4. A method for preparing the water-based polyacrylic resin for the colored stone metal tile according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: weighing raw materials according to mass parts, mixing a reactive emulsifier, part of deionized water and an initiator, stirring evenly, adding an acrylate monomer, an acrylic acid (ester) functional monomer and an acrylic acid phosphate monomer, and emulsifying to obtain a pre-emulsified liquid; heating the remaining deionized water, starting to drip the pre-emulsified liquid, controlling the dripping time, continuing to heat after the dripping is completed, adding zinc methacrylate after heat preservation reaction, continuing the reaction, and removing residual monomers after the reaction is terminated and cooling, adjusting the pH value and filtering to remove impurities, so as to prepare the water-based polyacrylic acid resin for the colored stone metal tile.

5. The preparation method according to claim 4, characterized in that: The heating temperature is heated to 81° C., the continued heating temperature is heated to 86° C., and the cooling temperature is cooled to 60° C.; and / or The emulsification time is 0.5h; and / or The dropping time is 2.5h; and / or The heat preservation reaction time is 1h; and / or The continued reaction is 1h; and / or The pH value is 7-8.

6. Use of the aqueous polyacrylic resin for colored stone metal tiles according to any one of claims 1 to 3 in preparing aqueous coatings for colored stone metal tiles.

7. A water-based coating for colored stone metal tiles, characterized in that: Calculated by mass, the composition comprises 30.0-45.0 parts of the water-based polyacrylic resin for the colored stone metal tiles according to any one of claims 1 to 3, 20.0-35.0 parts of filler, 1.5-3.0 parts of dispersant, 0.2-1.5 parts of defoamer, 1.5-3.0 parts of thickener, 0.1-1.5 parts of color paste and 15.0-25.0 parts of water.

8. The water-based coating for colored stone metal tiles according to claim 7, characterized in that: The filler is prepared by mixing heavy calcium, calcined kaolin and calcium fluoride in a mass ratio of 3.0:6.0:1.0; and / or The dispersant is a melamine water reducing agent; and / or The defoamer is a silicone defoamer; and / or The thickener is an alkali swelling thickener or a polyurethane thickener; and / or The color paste is phthalocyanine blue, iron red, chrome yellow or carbon black.

9. A method for preparing a water-based coating for a colored stone metal tile according to claim 7 or 8, characterized in that: The method comprises the following steps: weighing raw materials according to mass parts, adding water-based polyacrylic resin for colored stone metal tiles into water, stirring, adding defoaming agent and dispersant, continuing stirring, and slowly adding filler, stirring fully, dripping thickener diluted with water, adding color paste when the viscosity reaches 100±10ku, and finally stirring to obtain the water-based coating for colored stone metal tiles.

10. Use of the aqueous coating of the colored stone metal tile according to claim 7 or 8 in the field of roof decoration of new building materials.